Luseogliflozin, A Sodium Glucose Co-transporter 2 Inhibitor, Alleviates Hepatic Impairment in Japanese Patients with Type 2 Diabetes - Kusunoki, M.; Natsume, Y.; Sato, D.; Tsutsui, H.; Miyata, T.; Tsutsumi, K.; Suga, T.; Oshida, Y. (Drug Research, 2016)
Luseogliflozin, a selective inhibitor of sodium glucose co-transporter 2 (SGLT2), was previously shown to improve the blood glucose and hemoglobin A1c (HbA1c) levels of patients with type 2 diabetes in a clinical setting. Although patients with type 2 diabetes often have hepatic impairment, few reports have been published concerning the influence of luseogliflozin on HbA1c and hepatic function in patients with type 2 diabetes accompanied by hepatic impairment. The present study was undertaken to evaluate the influence of luseogliflozin on HbA1c and hepatic function in patients with type 2 diabetes divided into 2 groups according to hepatic function parameters (a normal group and an elevated group). In this study, luseogliflozin significantly improved both HbA1c and body weight to similar extents in both the normal group and the elevated group, accompanied by marked reductions in the aspartate aminotransferase (AST), alanine aminotransferase (ALT), and γ-glutamyl transpeptidase (γ-GTP) levels. These results suggested that luseogliflozin can be safely used in patients with type 2 diabetes who also exhibit hepatic impairment. The results additionally suggest the possibility that luseogliflozin might be capable of alleviating hepatic impairment in patients with type 2 diabetes.
Keywords: type 2 diabetes; sodium glucose co-transporter 2 inhibitor; hepatic function